Blending water- and nutrient-source wastewaters for cost-effective cultivation of high lipid content microalgal species Micractinium inermum NLP-F014. (December 2015) - Park, Seonghwan; Kim, Jeongmi; Yoon, Youngjin; Park, Younghyun; Lee, Taeho
Highlights: Influent of a domestic wastewater treatment plant was selected as a water source. A liquid fertilizer produced from swine wastewater was used as a nutrient source. No pretreatment was needed to use water-and nutrient-source wastewaters as media. M. inermum NLP-F014 grew well in the medium of the blended wastewaters. High biomass and lipid productivity were obtained at the optimum blending ratio. Abstract: The possibility of utilizing blended wastewaters from different streams was investigated for cost-efficient microalgal cultivation. The influent of a domestic wastewater treatment plant and the liquid fertilizer from a swine wastewater treatment plant were selected as water- and nutrient-source wastewaters, respectively. The growth of Micractinium inermum NLP-F014 in the blended wastewater medium without any pretreatment was comparable to that in Bold's Basal Medium. The optimum blending ratio of 5–15% (v v −1 ) facilitated biomass production up to 5.7 g-dry cell weight (DCW) L −1, and the maximum biomass productivity (1.03 g-DCW L −1  d −1 ) was achieved after three days of cultivation. Nutrient depletion induced lipid accumulation in the cell up to 39.1% (w w −1 ) and the maximum lipid productivity was 0.19 g-FAME L −1  d −1 . These results suggest that blending water- and nutrient-source wastewaters at a proper ratio without pretreatment can significantly cut costs in microalgae cultivation for biodiesel production.